Trinidad and Tobago. Significant achievements 2017 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2018)
The main activities carried out by the Institute in Trinidad and Tobago during 2017 are identified, with respect to the needs and interests of the country, strengthening issues such as governance, family farming, exports, leadership, financing, resilience against climate change and safety and food safety, through the Codex Alimentarius. Likewise, work was done on risk mapping, on the improvement of the dairy production chain, as well as on the raising of dairy goats and on forage production.